The Role of the Civil Service Police Unit in Implementing Regional Regulation No. 10 of 2014 concerning the Arrangement of Street Vendors in Ambon City - Hendry Selanno (Program Pascasarjana Universitas Negeri Makassar, 2019)
The main problem in this study is